2012
DOI: 10.1016/j.molcel.2012.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome-Activated Caspase 7 Cleaves PARP1 to Enhance the Expression of a Subset of NF-κB Target Genes

Abstract: Caspase 1 is part of the inflammasome, which is assembled upon pathogen recognition, while caspases 3 and/or 7 are mediators of apoptotic and nonapoptotic functions. PARP1 cleavage is a hallmark of apoptosis yet not essential, suggesting it has another physiological role. Here we show that after LPS stimulation, caspase 7 is activated by caspase 1, translocates to the nucleus, and cleaves PARP1 at the promoters of a subset of NF-κB target genes negatively regulated by PARP1. Mutating the PARP1 cleavage site D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 47 publications
8
109
0
Order By: Relevance
“…In addition, it was reported that caspase-7 activation after L. pneumophila infection was dependent on caspase-1 (34). Most recently, it was reported that caspase-7 is activated by caspase-1 after LPS stimulation although in that study the activated caspase-7 was shown to translocate to the nucleus where it played a nuclear function (33). Altogether, we therefore believe that many published reports support our finding that caspase-7 activation is dependent on caspase-1 activated during HDM administration.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, it was reported that caspase-7 activation after L. pneumophila infection was dependent on caspase-1 (34). Most recently, it was reported that caspase-7 is activated by caspase-1 after LPS stimulation although in that study the activated caspase-7 was shown to translocate to the nucleus where it played a nuclear function (33). Altogether, we therefore believe that many published reports support our finding that caspase-7 activation is dependent on caspase-1 activated during HDM administration.…”
Section: Discussionmentioning
confidence: 90%
“…As stated above, inflammasomes also promote cleavage of PARP1 (106)(107)(108). While it has yet to be studied in the context of RA, PARP1 proteolysis occurs during osteoclastogenesis (98,99,112,113).…”
Section: Skeletal Changes Associated With Excessive Inflammasome Actimentioning
confidence: 94%
“…Complex assembly activates caspase 1, which proteolytically processes pro-IL-1β and pro-IL-18. The NLRP3 inflammasome signaling cascade cleaves poly(ADP-ribose) polymerase 1 (PARP1) (106)(107)(108).…”
Section: Skeletal Changes Associated With Excessive Inflammasome Actimentioning
confidence: 99%
“…It has been shown that caspase-7 is involved in the maturation of L. pneumophila-containing phagosomes and induces cell death in infected macrophages (Akhter et al 2009). In addition, caspase-7 contributes to the activation of NF-jB through the cleavage of PARP1 in response to LPS stimulation in macrophages (Erener et al 2012); however, it is not clear whether this mechanism is involved in the inflammatory response towards genuine bacterial infection.…”
Section: Other Caspasesmentioning
confidence: 99%